Analysis of mixed connective disorder: a case report - Mohammed, Muzammil; Mohammed, Riyaz (International Journal of Research in Medical Sciences, 2024)
Mixed connective tissue disease (MCTD) as an autoimmune disorder with characteristics that resemble systemic sclerosis, systemic lupus erythematosus (SLE), and polymyositis. Due to this overlap, MCTD is often categorized as an overlap disease. As the disease progresses, symptoms may become more indicative of one of the three primary illnesses, accompanied by elevated levels of anti-U1RNP antibody. 30yrs female Patient presented with a classical malar rash as the initial presentation, followed by the development of a painful red lesion on the knuckles over a few weeks. Additionally, the patient observed a hypopigmented large lesion on the forearm resembling vitiligo, with a salt and pepper appearance. Upon clinical evaluation and further extensive investigation, the patient was diagnosed with mixed connective tissue disease (MCTD). On further evaluation the anti-U1RNP antibody, ANA, was positive and patient was treated on lines of MCTD. Patient responded well to the treatment. Our case suggests that mixed connective tissue disease if recognised early with symptoms and signs and workup we can prevent the shift to other connective tissue diseases over a long period; therefore, it is necessary to identify whether patients with mixed connective tissue disease fulfil the diagnostic criteria for other connective tissue diseases when new manifestations appear.